The prevalence and characteristics of intra-atrial right coronary artery anomaly in 9,284 patients referred for coronary computed tomography angiography - Opolski, Maksymilian P.; Pregowski, Jerzy; Kruk, Mariusz; Staruch, Adam D.; Witkowski, Adam; Demkow, Marcin; Hryniewiecki, Tomasz; Michalek, Piotr; Ruzyllo, Witold; Kepka, Cezary (European journal of radiology, 2014)
To determine the prevalence, radiologic patterns and clinical characteristics of intra-atrial right coronary artery (IARCA) among adult coronary computed tomography angiography (CCTA) population. We included 9,284 consecutive subjects who underwent CCTA at a single high-volume center. The presence of IARCA including the number, length and diameter of IARCA segments with accompanying atherosclerosis and coronary anomalies were evaluated. Additionally, clinical characteristics and midterm follow-up of IARCA patients were recorded. The IARCA prevalence was 0.15% (14/9,284) with 15 intra-atrial segments. The intra-atrial segment length ranged from 14 to 53mm, and the mean diameter proximal to the entry site was 3.3±0.7mm. IARCA was more often associated with intramuscular course of the left anterior descending coronary artery (29% vs. 4%, p=0.001) and anomalous origin of the left circumflex artery from the right aortic sinus (14% vs. 0.3%, p=0.001) compared with non-IARCA cases. The majority of IARCA patients were women (86%) presenting with supraventricular arrhythmia (71%). Compared with computed tomographic population without IARCA, IARCA subjects were younger (60±12 vs. 54±14 years, p=0.037) and more often women (51% vs. 86%, p=0.013). At a mean of 20 months follow-up of IARCA patients there were no adverse cardiac events except for supraventricular tachycardia episodes occurring in 36% of subjects. IARCA occurs rarely and is often associated with additional coronary anomalies. The clinical profile of IARCA patients is most often represented by middle-aged women with supraventricular arrhythmia showing favorable midterm prognosis.